Epilithic Diatoms of Lake Hazar (Elazığ-Türkiye) - Çalışkan, Hakan; Cetin, Ahmet Kadri (Uğur ÇAKILCIOĞLU, 2025)
In this study, the epilithic diatoms of Lake Hazar, one of the most important surface water resources in the Eastern Anatolian region of Türkiye, were investigated. As a result of the examination of the epilithic diatom flora, it was found that the diatom diversity is quite high and the epilithic diatoms are represented by 61 species belonging to 36 genera. Navicula (7 spp.), Epithemia (6 spp.) and Cymbella (3 spp.) were the most abundant genera. In Hazar Lake, centric diatoms were represented by Stephanocyclus meneghinianus and Cyclostephanos dubius. It was determined that a significant proportion of these species were cosmopolitan. It was found that some of the species found in Lake Hazar are ecologically oligotrophic species that prefer alkaline water.

In this study, the epilithic diatoms of Lake Hazar, one of the most important surface water resources in the Eastern Anatolian region of Türkiye, were investigated. As a result of the examination of the epilithic diatom flora, it was found that the diatom diversity is quite high and the epilithic diatoms are represented by 61 species belonging to 36 genera. Navicula (7 spp.), Epithemia (6 spp.) and Cymbella (3 spp.) were the most abundant genera. In Hazar Lake, centric diatoms were represented by Stephanocyclus meneghinianus and Cyclostephanos dubius. It was determined that a significant proportion of these species were cosmopolitan. It was found that some of the species found in Lake Hazar are ecologically oligotrophic species that prefer alkaline water.
Epilithic Diatoms of Lake Hazar (Elazığ-Türkiye)
Keywords: Enzymes; Enzimler; Conservation and Biodiversity; Koruma ve Biyolojik Çeşitlilik